Family Business Succession: What’s Motivation Got to Do With It? - Gagné, Marylène; Marwick, Connor; Brun de Pontet, Stéphanie; Wrosch, Carsten (SAGE, 2021)
Family businesses represent 80% of global business structures, but the low rate of successful transgenerational succession can have drastic implications for employees and local economies. A 12-year longitudinal study of 89 Canadian family businesses revealed that successors’ confidence and perceptions of incumbent support predicted successor intrinsic motivation to take over the business, which in turn predicted whether the business was successfully transferred 12 years later. Incumbent support and intrinsic motivation mediated the relation between incumbent trust in the successor and successful business succession. This study demonstrates the dual importance of incumbent and successor psychological states in determining succession outcomes.